The Protection of the Defendant’s Rights in Criminal Trial by Default — From the Perspective of Due Process - Yangyang Bu (Теоретическая и прикладная юриспруденция)
Due to the change of the traditional procedural structure of the complete three parties of prosecution, defense and trial, criminal trial in absentia may result in the neglect of the rights protection measures due to the absence of the defendant in trial, and thus further impacts several principles and norms under the due process. Based on the criminal procedure system and even the reform of the entire judicial system, the discussion on the criminal trial in absentia should not be conﬁned to the basic frame of normal bench trial paradigm by due process, the possible adverse consequences should not be taken as the inevitable argument for criticizing the system, but rather a rational and neutral position, return to the original point of the system, seek the basic principles involved in the criminal trial in absentia, and respond to many doubts that the absent defendant’s rights are bound to fall, and thinking dialectically on this basis, from the two dimensions of system function, value presetting and perfection of existing speciﬁcations, deduces and sums up the internal logic of this system in its normative construction, system operation and internal and external harmony, focusing on strengthening the rights protection of the defendant at the times.